2022
DOI: 10.21037/cco-21-166
|View full text |Cite
|
Sign up to set email alerts
|

Current status and future perspective of neoadjuvant therapy in locally advanced and borderline resectable pancreatic adenocarcinoma: a narrative review

Abstract: Background and Objective: The concept of neoadjuvant approach for patients with locally advanced pancreatic cancer (LAPC) has been evolving with the advancement in therapeutic modalities. In this narrative review, we aimed to discuss the updates and future perspectives on the treatment of LAPC. Methods:We discussed the recent literature and up-to-date evidence along with the future perspectives for the treatment of LAPC using the neoadjuvant approach. Reviewed literatures were searched by systematic search of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…These regimens used as preoperative chemotherapy improved the resectability rate of initially unresectable or borderline resectable disease compared with previous regimens of mainly the single agent of gemcitabine, and lots of clinical trials showed better survival compared with upfront surgery. On the other hand, as Hyung et al suggested, the effect of radiotherapy remains controversial and further studies are expected (2). In this special series we did not focus on the radiotherapy.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…These regimens used as preoperative chemotherapy improved the resectability rate of initially unresectable or borderline resectable disease compared with previous regimens of mainly the single agent of gemcitabine, and lots of clinical trials showed better survival compared with upfront surgery. On the other hand, as Hyung et al suggested, the effect of radiotherapy remains controversial and further studies are expected (2). In this special series we did not focus on the radiotherapy.…”
mentioning
confidence: 86%
“…In this series "Pre-and post-operative treatment for pancreatic cancer", we publish four insightful narrative reviews by the experts from medical oncology, surgical oncology, and pathology (1)(2)(3)(4). We respectfully express my gratitude to all authors contributing to this series.…”
mentioning
confidence: 99%
“…In our previous phase 2 clinical trial of 44 patients with BRPC treated with neoadjuvant mFOLFIRINOX followed by surgery and adjuvant gemcitabine, the 1-year progression-free survival (PFS) rate was 52.3% (95% confidence interval [CI], 37.6 to 67.0) and 27 patients (61.4%) received surgical resection [ 5 ]. Other treatment regimens, including gemcitabine plus nab-paclitaxel or the addition of subsequent chemoradiation can be used, although there is currently no evidence to guide the selection of specific regimens [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In certain cases of BRPC and LAPC, chemoradiotherapy may increase the chances of achieving a margin-negative resection in patients who are being considered for surgery(Murphy, Wo et al 2019, Murphy, Wo et al 2018). However, the role of chemoradiation/radiotherapy has been rarely investigated as the second-line therapy in patients with LAPC who failed on induction chemotherapy(Hyung, Lee et al 2022…”
mentioning
confidence: 99%